Multifunctional films from porous matrices - Silva, Carla Florbela Ferreira Pinto da (2013)
Multiferroic materials, that exhibit both ferroelectric and ferromagnetic properties, have attracted considerable interest in the scientific community due to its potential for novel applications in electronic devices as well as for physics and materials science underlying its multifunctionality. In multiferroic composites, the coupling magnetoelectric is due to elastic interaction between ferromagnetic and ferroelectric phases caused by the piezoelectric and magnetostrictive effect. The strategy of this work encompass: i) the preparation of porous thin films of ferroelectric barium titanate; ii) the synthesis of magnetic nanoparticles to be incorporated in the previous porous films and iii) the functionalization of the ferroelectric porous matrix aiming to fabricate multiferroic nano composite. The composite system BaTiO3-CoFe2O4 was chosen due to the piezoelectricity of BaTiO3, thus allowing strong elastic interaction between the two phases, and good magnetostriction of CoFe2O4. For materials synthesis, easy, environmental friendly and cost effective methodologies were adopted: i) evaporation induced selfassembly (EISA) assisted by dip-coating to prepare porous ferroelectric matrix; ii) hydrothermal synthesis to prepare magnetic nanoparticles and iii) electrophoretic deposition for functionalization. The BaTiO3 thin films were obtained using polystyrene-poly(ethylene oxide) block co-polymer (PS-b-PEO) as template to create porosity. The effect of a polymer with different molecular weights (Mw) in the creation of porosity, concentration of block co-polymer, type of annealing and withdrawal rate of the dipcoating were studied in this work. The porous microstructure of BaTiO3 thin films were studied by SEM. Decomposition of the solvents and BaTiO3 crystallization was studied by DTA/TGA. The topography and piezoelectric behaviour of porous films was analysed by AFM/ PFM. CoFe2O4 nanoparticles were obtained by hydrothermal synthesis. The effect of temperature and time of the hydrothermal synthesis, the addition of polyvinylpyrrolidone (PVP) as additive with different concentrations, and effect of precipitating (NaOH) and Co2+/Fe3+ concentration were studied in order to prepare nanoparticles with desired size and magnetic properties. The shape, size, dispersion and crystallinity of the nanoparticles were studied by various techniques such as TEM, BET and XRD. The crystallite size was calculated by Scherrer equation. The magnetic properties were evaluated by SQUID magnetometer. The results show that with the increase of temperature and time synthesis the particle and crystallite size increases too. The saturation magnetization depends of particles size, increasing with particle size increase. The increasing particle size from 12.9 to 16.1 nm provokes an increase in saturation magnetization from 53.7 to 73.2 emu/g. In time of hydrothermal synthesis studies, it was observed that a antiferromagnetic phase appear, hematite (α-Fe2O3). The presence of this phase damaged drastically the magnetic properties to 8.2 emu/g in the case of a sample prepared over 24 h. The PVP addition does not affect the shape of nanoparticles however favours their growth from 20.1 to 23.6. In term of magnetic properties, no influence was observed. The increase of Co2+/Fe3+ and NaOH concentration induces growth of nanoparticles. The functionalization of BaTiO3 films was made by electrophoretic deposition (EPD). Initially, the process optimization was necessary by studying the different parameters related with deposition such as: applied voltage, deposition time and suspension type. This studies permits to conclude that with time increasing, the amount of nanoparticles deposited increases too. It was observed that, despite the optimization of EPD, it is important the use a good quality substrate that can afford voltage application.